2017
DOI: 10.1177/0363546517713176
|View full text |Cite
|
Sign up to set email alerts
|

A Traffic Light Grading System of Hip Dysplasia to Predict the Success of Arthroscopic Hip Surgery

Abstract: Overall, the 7-year hip survival rate in hip dysplasia appears inferior compared with that reported in femoroacetabular impingement (78%). Hip arthroscopic surgery is associated with an excellent chance of hip preservation in mild dysplasia (green zone: AI = 0°-15°, LCEA = 15°-25°) and no articular wear. The authors advise that the greatest caution should be used when considering arthroscopic options in cases of severe dysplasia (red zone: AI >20° and/or LCEA <10°).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…Grammatopoulos et al 21 performed a retrospective case-control study of 111 hips with an acetabular index >10° and/or LCEA <25° that underwent hip arthroscopy. The authors identified 33 hips with failed arthroscopic treatment, requiring hip arthroplasty at a mean 4.5-year follow-up.…”
Section: Defining Frank Hip Dysplasia and Bhd With Radiographic Parammentioning
confidence: 99%
“…Grammatopoulos et al 21 performed a retrospective case-control study of 111 hips with an acetabular index >10° and/or LCEA <25° that underwent hip arthroscopy. The authors identified 33 hips with failed arthroscopic treatment, requiring hip arthroplasty at a mean 4.5-year follow-up.…”
Section: Defining Frank Hip Dysplasia and Bhd With Radiographic Parammentioning
confidence: 99%
“…Grammatopoulos et al 20 conducted a study to identify radiographic and intraoperative features that could predict the success of hip preservation with arthroscopic surgery. Using a mean follow-up of 4.5 years, they concluded that arthroscopic hip surgery can be associated with an excellent chance of hip preservation with a Tönnis angle <15° and an LCEA >25° in the absence of hip instability.…”
Section: Discussionmentioning
confidence: 99%
“…Features of dysplasia on pre-operative radiographs seem to suggest limited success for hip arthroscopy; Larson et al [ 20 ] showed that the more severe the dysplasia, the less the likelihood that arthroscopy can be effective as hip preserving surgery. This, however, appears to represent a point on a spectrum and we feel that hip arthroscopy still has a role in the management of patients with mild dysplasia although this needs further exploration [ 21 ].…”
Section: Discussionmentioning
confidence: 99%